Six Novel ATM Gene Variants in Sri Lankan Patients with Ataxia Telangiectasia - D. Hettiarachchi; Hetalkumar Panchal; B. A. P. S. Pathirana; P. D. Rathnayaka; A. Padeniya; P. S. Lai; V. H. W. Dissanayake (Case Reports in Genetics)
Introduction. Ataxia telangiectasia is a rare genetic condition with an estimated prevalence of 1 in 40,000–100,000 live births. This condition predominantly affects the nervous and immune systems. It is characterized by progressive ataxia beginning from early childhood. The neurological deficit associated with this condition affects one’s balance, coordination, walking, and speech and can be accompanied by chorea, myoclonus, and neuropathy. They may also have ocular telangiectasias and high levels of blood alpha-fetoprotein (AFP). The ataxia telangiectasia mutated gene (ATM) is associated with this condition and codes for the ATM protein which is a phosphatidylinositol 3-kinase. This gene occupies 150 kb on chromosome 11q22–23 and contains 66 exons encoding a 13 kb transcript. ATM is a relatively large protein with a molecular weight of 350 kDa and 3,056 amino acids. Methods. Four patients of Sri Lankan origin presenting with features suggestive of ataxia telangiectasia were referred to our genetics center for specialized genetic counseling and testing. Whole-exome sequencing followed by Sanger sequencing was used to confirm the candidate variants. Protein modeling and genotype to phenotype correlation was performed in the identified variants. Results. We observed 6 novel ATM gene variants in four patients with ataxia telangiectasia. The identified variants are as follows: homozygous c.7397C > A (p.Ala2466Glu) and c.510_511delGT (p.Tyr171fs) and compound heterozygous c.5347_5350delGAAA (p.Glu1783fs), c.8137A > T (p.Arg2713∗) and c.1163A > C (p.Lys388Thr), and c.5227A > C (p.Thr1743Pro). Variant analysis was followed by modeling of the native and altered protein structures. Conclusion. We report novel ATM gene variants that have implications on the molecular diagnosis of ataxia telangiectasia.